2012
DOI: 10.1124/mol.112.078626
|View full text |Cite
|
Sign up to set email alerts
|

Functional Selectivity in Serotonin Receptor 2A (5-HT2A) Endocytosis, Recycling, and Phosphorylation

Abstract: G protein-coupled receptor (GPCR) signaling is modulated by endocytosis and endosomal sorting of receptors between degradation and recycling. Differential regulation of these processes by endogenous ligands and synthetic drugs is a poorly understood area of GPCR signaling. Here, we describe remarkable diversity in the regulation of trafficking of GPCR induced by multiple ligands. We show that the serotonin receptor 2A (5-HT 2A ), a prototypical GPCR in the study of functional selectivity at a signaling recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 51 publications
(53 reference statements)
1
37
0
Order By: Relevance
“…To our knowledge, no study has so far compared the ability of hallucinogenic and nonhallucinogenic compounds to desensitize 5-HT 2A receptors. Nonetheless, the present findings are consistent with a recent study, which demonstrated that DOI was less efficient than 5-HT to internalize eGFP-tagged 5-HT 2A receptors stably expressed in HEK-293 cells (27). They also provide convergent evidence indicating that the different effects of hallucinogenic versus non hallucinogenic agonists upon receptor desensitization reflect their differential capacity to promote Ser 280 phosphorylation: (1) mutating Ser 280 into alanine or aspartate abolished the difference in the agonist effects upon receptor desensitization; (2) hallucinogens were able to desensitize S 280 A receptor to an extent comparable to that induced by nonhallucinogenic agonists in cells expressing wild type receptor and (3) nonhallucinogenic agonists did not promote desensitization of the Ser 280 D receptor mutant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To our knowledge, no study has so far compared the ability of hallucinogenic and nonhallucinogenic compounds to desensitize 5-HT 2A receptors. Nonetheless, the present findings are consistent with a recent study, which demonstrated that DOI was less efficient than 5-HT to internalize eGFP-tagged 5-HT 2A receptors stably expressed in HEK-293 cells (27). They also provide convergent evidence indicating that the different effects of hallucinogenic versus non hallucinogenic agonists upon receptor desensitization reflect their differential capacity to promote Ser 280 phosphorylation: (1) mutating Ser 280 into alanine or aspartate abolished the difference in the agonist effects upon receptor desensitization; (2) hallucinogens were able to desensitize S 280 A receptor to an extent comparable to that induced by nonhallucinogenic agonists in cells expressing wild type receptor and (3) nonhallucinogenic agonists did not promote desensitization of the Ser 280 D receptor mutant.…”
Section: Discussionsupporting
confidence: 93%
“…Given the role of PKC in 5-HT 2A receptor desensitization and internalization and the importance of the 5-HT 2A receptor i3 loop in the regulation of receptor responsiveness (26–29), we next examined whether hallucinogenic and nonhallucinogenic agonists differentially modulate receptor desensitization. Pretreatment of HEK-293 cells with either lisuride or ergotamine for 1 h, followed by extensive drug washout, inhibited inositol phosphate production induced by a further exposure of cells to 5-HT, whereas pretreating cells with DOI or LSD did not significantly affect the 5-HT response (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the 5-HT 2A R mRNA levels are almost twice as high compared with the other investigated targets. We speculate that high mRNA levels enable the system to regulate synaptic 5-HT 2A R levels quickly, consistent with the ligand-induced endocytosis and recycling of 5-HT 2A R (Raote et al, 2013). We observed a moderate correlation association between 5-HT 4 R mRNA and 5-HT 4 R protein density (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…For example, PKC phosphorylation of serine residue S291 in the 5-HT 2A receptor is also thought to play a role in modulation of receptor signaling. Using five different ligands that activate the 5-HT 2A receptor, Raote et al (2013) showed that different biochemical pathways are involved in receptor trafficking. These investigators used the fluorescence of rat 5-HT 2A enhanced green fluorescent protein (EGFP) to follow receptor internalization.…”
Section: Nicholsmentioning
confidence: 99%